Collective Polarization of Cancer Cells at the Monolayer Boundary - Liu-Yuan Guan; Jian-Qing Lv; De-Qing Zhang; Bo Li (Micromachines, 2021)
Cell polarization, a process depending on both intracellular and intercellular interactions, is crucial for collective cell migration that commonly emerges in embryonic development, tissue morphogenesis, wound healing and cancer metastasis. Although invasive cancer cells display weak cell–cell interactions, they can invade host tissues through a collective mode. Yet, how cancer cells without stable cell–cell junctions polarize collectively to migrate and invade is not fully understood. Here, using a wound-healing assay, we elucidate the polarization of carcinoma cells at the population level. We show that with loose intercellular connections, the highly polarized leader cells can induce the polarization of following cancer cells and subsequent transmission of polarity information by membrane protrusions, leading to gradient polarization at the monolayer boundary. Unlike the polarization of epithelial monolayer where Rac1/Cdc42 pathway functions primarily, our data show that collective polarization of carcinoma cells is predominantly controlled by Golgi apparatus, a disruption of which results in the destruction of collective polarization over a large scale. We reveal that the Golgi apparatus can sustain membrane protrusion formation, polarized secretion, intracellular trafficking, and F-actin polarization, which contribute to collective cancer cell polarization and its transmission between cells. These findings could advance our understanding of collective cancer invasion in tumors.